A flexible and fully recyclable transparent conductive organogel based on KI-containing glycerol with excellent anti-freezing and anti-drying behavior. Issue 41 (28th September 2022) - He, Jiaqing; Yang, Kaixiang; Zhou, Qiang; Xie, Yongjun; Zou, Gang; Yang, Haiyang
Abstract : As a potential candidate for electronic sensors, mechanically robust and flexible conductive hydrogels or organohydrogels have gained increasing attention in recent years. Abstract : As a potential candidate for electronic sensors, mechanically robust and flexible conductive hydrogels or organohydrogels have gained increasing attention in recent years. Herein, a new type of flexible and fully recyclable transparent conductive organogel based on KI-containing glycerol was fabricated by one-pot polymerization of N -hydroxyethyl acrylamide (HEAA) dissolved in KI-containing glycerol. Due to the absence of water, the organogel exhibited outstanding anti-freezing and anti-drying behavior. In fact, the mechanical robustness, conductivity, and transparency of the organogel could be well maintained even at −80 °C or 100 °C. Moreover, the organogel also exhibited high sensitivity and reliability and wide sensing ranges for monitoring and distinguishing various physiological signals and human motions. Of particular interest was that the organogel was sensitive to human sweat, due to the adsorption of salted water. Composed of non-covalent cross-linking sites, the organogel was also fully recyclable in polar solvents and could be remolded accordingly. Our experimental results indicated that organogels, instead of hydrogels or organohydrogels, could also be endowed with excellent mechanical strength, conductivity, and performance even under critical conditions. The design and practical application of transparent, environmental tolerant, and stretchable electronic sensors based on organogels will be enhanced and advanced significantly.